10th European Conference on Mixing : proceedings of the 10th European conference, Delft, the Netherlands, July 2-5, 2000 - Akker, Hendrikus Egidius Antonia van den, 1950-; Derksen, J. J. (Elsevier, 2000)
Traditionally, fluid mixing and the related multiphase contacting processes have always been regarded as an empirical technology. Many aspects of mixing, dispersing and contacting were related to power draw, but understanding of the phenomena was limited or qualitative at the most. In particular during the last decade, however, plant operation targets have tightened and product specifications have become stricter. The public awareness as to safety and environmental hygiene has increased. The drive towards larger degrees of sustainability in the process industries has urged for lower amounts of solvents and for higher yields and higher selectivities in chemical reactors. All this has resulted in a market pull: the need for more detailed insights in flow phenomena and processes and for better verifiable design and operation methods. Developments in miniaturisation of sensors and circuits as well as in computer technology have rendered leaps possible in computer simulation and animation and in measuring and monitoring techniques. This volume encourages a leap forward in the field of mixing by the current, overwhelming wealth of sophisticated measuring and computational techniques. This leap may be made possible by modern instrumentation, signal and data analysis, field reconstruction algorithms, computational modelling techniques and numerical recipes.